Asas Kemaslahatan dalam Penyelesaian Tindak Pidana Perundungan oleh Santri Berdasarkan MAQĀṢID SYARĪ’AH - Lahiyah, Ilham; Muhammadi, Fauzan; Muhammad Habibi Miftakhul Marwa; Kurnia Dewi Anggraeny (Fakultas Hukum Universitas Muhammadiyah Sorong, 2024)
Apart from the main aim of Islamic boarding schools for Islamic development, carrying out Islamic boarding schools often encounters problems, for example, cases of criminal acts by students. Thus, criminal acts that occur in the Islamic boarding school environment become insignificant and normal. One of the criminal problems that often occurs in Islamic boarding schools is bullying. Islamic boarding schools in Babakan, Ciwaringin, Cirebon area have various areas, buildings, and numbers of students. Criminal cases like bullying are common to occur in the boarding school environment. Therefore, this research aims to determine the application of Islamic boarding school principles of virtue in resolving student bullying cases and to determine Islamic boarding school principles of virtue in resolving Islamic boarding school bullying cases in terms of maqāṣid syarī'ah. This research is a qualitative study using a conceptual approach and a statutory approach. This method is supported by primary and secondary data. The primary data were collected through interviews with Islamic boarding school managers and students, while the secondary data were obtained through literature studies from books, journals, articles, and else related to this research. This research found that bullying still commonly happens in Islamic boarding schools. Efforts to resolve the problems by the Islamic Boarding Schools are carried out using internal processes such as discussion or non-physical punishment in accordance with the Islamic Boarding School's internal regulations. This is considered to be in line with the Principles of Virtue as stated in the Islamic Boarding School Law. In addition, the existence of the Islamic Boarding School Law has not been widely known by the elements within the Islamic Boarding Schools. However, what the Islamic Boarding Schools implement in resolving bullying cases has accommodated the concept of protecting the soul contained in maqāṣid syarī'ah. Keywords: Pesantren; Maṣlaḥah; Bullying; Maqāṣid